Innovation in Catalytic Converters for Motorcycles in an Effort to Reduce Air Pollution from Combustion - Silvia Ekasari; Eva Weddakarti; Ahsani Maulidina (Research in Chemical Engineering, 2025)
Air pollution remains one of the most challenging environmental issues. Motor vehicle exhaust gases contribute around 70%–80% of air pollution, while industrial activities contribute only 20%–30%. Exhaust emissions from incomplete combustion include carbon monoxide (CO), hydrocarbons (HC), nitrogen oxides (NOx), and lead (Pb), which are harmful to health and the environment. One promising solution is the installation of catalytic converters. This study investigates the effectiveness of catalytic converters made of stainless steel coated with chromium and copper in reducing emissions from motorcycle exhaust systems. The experimental results show that the catalytic converter significantly reduced harmful gases: CO decreased by 44%, HC decreased by 63.65%, while CO₂ increased from 7.1% to 11.2%, indicating successful oxidation. These findings highlight the catalytic converter’s role in reducing harmful emissions and its potential to mitigate air pollution from motorcycles.